Controlling Pattern Formation in Nanoparticle Assemblies via Directed Solvent Dewetting - Martin, CP; Blunt, MO; Pauliac-Vaujour, E; Stannard, A; Moriarty, P; Vancea, I; Thiele, U (American Physical Society, 2007)
We have achieved highly localised control of pattern formation in two dimensional nanoparticle assemblies by direct modification of solvent dewetting dynamics. A striking dependence of nanoparticle organisation on the size of atomic force microscope-generated surface heterogeneities is observed and reproduced in numerical simulations. Nanoscale features induce rupture of the solvent-nanoparticle film, causing the local flow of solvent to carry nanoparticles into confinement. Microscale heterogeneities instead slow the evaporation of the solvent, producing a remarkably abrupt interface between different nanoparticle patterns.